PERAN ISTRI SEBAGAI PENCARI NAFKAH UTAMA KELUARGA DALAM PERSPEKTIF HUKUM ISLAM - Suaib Lubis; Abdullah Sani Kurniadinata; Suci Ramadani (Prodi Hukum Ekonomi Syariah (Muamalah), 2018)
This study was conducted with the aim of knowing the provisions of family living according to Islamic law, what factors are behind the wife's profession as a female worker in Tangkahan Durian Village, Brandan Barat District and how Islamic law reviews the wife as a female worker in earning a living for the family. This research is an analytical descriptive study using a qualitative research approach that focuses its study on the phenomenon of the number of working wives that occurs in Tangkahan Durian Village, West Brandan District. To assist this research, data were collected through observation, interviews and documentation related to the problem and then analyzed. The results of the study show that, in general they understand that working to provide for the family is an obligation for every head of the family, but many of them are not aware of the magnitude of this obligation, so there are still some heads of families who do not work while their wives work abroad as female workers to earn a living.